2020
DOI: 10.3390/ijerph17239020
|View full text |Cite
|
Sign up to set email alerts
|

Association between Crash Attributes and Drivers’ Crash Involvement: A Study Based on Police-Reported Crash Data

Abstract: Understanding the association between crash attributes and drivers’ crash involvement in different types of crashes can help figure out the causation of crashes. The aim of this study was to examine the involvement in different types of crashes for drivers from different age groups, by using the police-reported crash data from 2014 to 2016 in Shenzhen, China. A synthetic minority oversampling technique (SMOTE) together with edited nearest neighbors (ENN) were used to solve the data imbalance problem caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…This may be due to the rush-hour that often occurs as individuals rush back home as work ends at around 5 or 6 in the evening. This was similar to the results of the study by 23 where they observed a higher association of road crashes during the latter half of the day among young and middle-aged drivers. Younger drivers, in particular, were also more likely to be involved in a car crash during the first few hours' past midnight.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This may be due to the rush-hour that often occurs as individuals rush back home as work ends at around 5 or 6 in the evening. This was similar to the results of the study by 23 where they observed a higher association of road crashes during the latter half of the day among young and middle-aged drivers. Younger drivers, in particular, were also more likely to be involved in a car crash during the first few hours' past midnight.…”
Section: Discussionsupporting
confidence: 91%
“…36 Driver behavior also has an effect on pedestrian safety as multiple studies have reported drivers colliding with pedestrians due to poorer experience and risky behaviors on the road. 7,19,23,37 These studies show that pedestrians remain as one of the most vulnerable, yet most neglected road user in terms of road infrastructure design that should promote their safety.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To integrate the advantages of over-sampling and over-sampling, the SMOTE-ENN method firstly uses SMOTE method to achieve over-sampling on the minority class samples and then finishes under-sampling on the majority class samples by using ENN method. This method preserves the features of majority samples and increases the characteristics of minority samples, has good classification performance for unbalanced datasets [ 38 ], and it is widely used in traffic safety analysis [ 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lombardi et al [18] analyzed 120,809 fatal accidents in the US during the period 2011-2014 and found that most drivers in fatal intersection crashes were either teenage drivers or older drivers. Li et al [19] found that different crash types were affected by different factors. For instance, the drivers in crashes that took place on rainy days were in many cases young drivers or old drivers.…”
Section: Related Workmentioning
confidence: 99%